Ensino empreendedor: visão e percepção dos alunos finalistas do curso noturno de administração da UFAM - Souza, Paulo Rennan Almeida de (Brasil, 2024)
This study analyzes the profile and entrepreneurial vision of final year students of the evening Administration course at UFAM, also investigating their perceptions about the entrepreneurship teaching offered. The research is justified by its growing relevance in the job market and in the academic environment. An exploratory and descriptive approach was used, including bibliographical review and application of a structured questionnaire to a convenience sample made up of 68 students considered finalists. The results indicate a general positive perception regarding the entrepreneurial education offered, although little interest in traditional entrepreneurship is observed. As a proposal, the students mentioned the need for more subjects that address entrepreneurial education, in addition to holding events and projects that reinforce entrepreneurial practice.